Functional assessment of temperature-gated ion-channel activity using a real-time PCR machine - Derek S. Reubish; Daniel E. Emerling; Jeff DeFalco; Daniel Steiger; Cheryl L. Victoria; Fabien Vincent (BioTechniques)
The functional activity of a number of ion channels is highly sensitive to large changes in temperature. Foremost among these are the thermosensing TRP channels which include cold- (TRPM8, TRPA1), warmth- (TRPV3, TRPV4), and heat-sensing (TRPV1, TRPV2) members. TRPV1, also known as the vanilloid receptor (VR1), is activated by ligands such as capsaicin, acidic pH, and heat (an increase in temperature to ∼42°C will lead to channel opening). Screening against the thermal gating of TRPV1 is generally performed using perfusion systems or water baths for temperature control, in conjunction with electrophysiology or Ca2 + influx readouts for direct functional assessment. These approaches are very useful, but have limited throughput or minimal thermo-temporal control. A standard real-time PCR machine with standard microplates allowed us to combine fluorescent Ca2 + detection with precise temperature manipulation to develop a homogeneous (Z′ = 0.53), cell-based assay that uses temperature as the agonist. A temperature response curve of TRPV1 was obtained, which provided a T50 of 46.1°C, and IC50 values against heat agonism were determined for known TRPV1 antagonists. Furthermore, we expanded this approach to a cold-activated ion channel, TRPM8. We developed and validated an analytical technique with broad applications for the study and screening of temperature-gated ion channels.